Maternal and grandmaternal age influence offspring fitness in Drosophila. - Hercus, M J (2000)
The influence of maternal and grandmaternal age on progeny egg-to-adult viability was assessed in Drosophila serrata. Viability in progeny decreased with increasing maternal age. The potential for cumulative age effects was investigated in two environments, one of which involved nutrient and cold stress. Environment influenced viability and female age influenced progeny egg-to-adult viability across one generation. The influence on viability was cumulative across two generations. Females from old mothers, who also had old grandmothers, had the lowest viability in both environments. Grandmaternal effects were associated with a decrease in egg hatch rate whereas maternal effects also involved larval-to-adult viability. The age of the mother and grandmother should be taken into account when evaluating life-history traits in Drosophila.